ANALISIS STRATEGI GURU DALAM MEMBELAJARKAN SISWA MEMBACA PERMULAAN DI SDN 18 TUBUNG - Anugerah, Wahyuni; Ason, Ason; Lestari, Novika (STKIP Melawi, 2023)
This study aims to determine the teacher's strategy in teaching students to read the beginning at SDN 18 Tubung. The research was carried out in the lower grades especially in the first grade. This research is a type of qualitative research where the research results are described in accordance with reality in the field. The subject in this study is a Class I Teacher and the object of this study is the teacher's strategy in teaching students to read the beginning. Data collection techniques are carried out by interviews, and observation and documentation. The research instruments used are interview guideline sheets and observation sheets. Data processing techniques go through three stages, namely data reduction, data presentation and drawing conclusions.The results of this study show that: 1) The planning stage, teachers have not been able to make learning designs; 2) The stage of learning implementation, it was found that in teaching students to read the beginning in class I, the teacher used various strategies including letter card strategies, syllable cards, and word cards, singing strategies, alphabetical methods, and syllable methods; 3) Learning evaluation stage, the teacher provides a formative evaluation by asking students to take turns reading the letters listed on the board or taking The letter cards available are as the teacher mentioned.